Management of Cancer-Associated Venous Thrombosis: A Nationwide Survey among Danish Oncologists - Højen, Anette Arbjerg; Overvad, Thure Filskov; Nybo, Mads; Kümler, Thomas; Rasmussen, Morten Schnack; Christensen, Thomas Decker; Larsen, Torben Bjerregaard (TH Open, 2021)
Background Treatment patterns for cancer-associated venous thrombosis (CAT) has been shown to be nonconsistent with contemporary guideline recommendations, resulting in poor patient outcomes.Objectives The study aimed to describe contemporary CAT management in Danish oncology departments and identify knowledge gaps and inconsistencies between guidelines and clinical practice.Patients and Methods A survey questionnaire in Danish was developed based on contemporary national guidelines. Using an open recruitment strategy, invitations to participate in the electronic survey were sent to physicians employed at oncology departments in Denmark in winter of 2018/2019. The questionnaire was based on current national guidelines and included 10 items with multiple choices and a free-text option to specify or comment. The questionnaire was pilot-tested by a junior and senior oncologist.Results A total of 142 physicians completed the survey, representing all Danish geographical regions and various seniority. The majority reported that CAT was treated and followed up in oncology departments. However, 36.6% of the physicians were unaware of the existence of designated cancer thrombosis guidelines. Risk of venous thrombosis was generally assessed without diagnostic scores. Almost all (98.6%) reported low-molecular-weight heparin to be first-line treatment for CAT. Treatment duration seemed wrongly influenced by subtype of venous thrombosis, and 44.5% responded that thromboprophylaxis among hospitalized patients was substantially underused.Conclusion The variability in the daily clinical management of CAT demonstrated through this survey indicates a potential to increase awareness of available guidelines, standardized use of inpatient thromboprophylaxis, and organized treatment and follow-up in a multidisciplinary setting, which would potentially improve management of CAT in Denmark.
Keywords: venous thromboembolism; cancer associated venous thrombosis; practice guideline; cancer; survey